Perspectives of older adults with chronic disease on the use of wearable technology and video games for physical activity. (May 2021) - Simmich, Joshua; Mandrusiak, Allison; Russell, Trevor; Smith, Stuart; Hartley, Nicole
Background: There is increasing interest in technology to deliver physical rehabilitation and allow clinicians to monitor progress. Examples include wearable activity trackers and active video games (AVGs), where physical activity is required to play the game. However, few studies have explored what may influence the effectiveness of these as technology-based physical activity interventions in older adults with chronic diseases. Objective: This study aimed to explore: 1) perceptions about wearable physical activity trackers; 2) perceptions about using technology to share physical activity information with clinicians; 3) barriers and motivators to playing games, including AVGs for rehabilitation. Methods: Qualitative study based on semi-structured interviews with older adults ( n = 19) with chronic obstructive pulmonary disease (COPD). Results: Wearable activity trackers were perceived as useful to quantify activity, facilitate goal-setting, visualize long-term improvements and provide reminders. Participants generally wished to share data with their clinicians to gain greater accountability, receive useful feedback and improve the quality of clinical care. Participants were motivated to play games (including AVGs) by seeking fun, social interaction and health benefits. Some felt that AVGs were of no benefit or were too difficult. Competition was both a motivator and a barrier. Conclusions: The findings of the present study seek to inform the design of technology to encourage physical activity in older adults with chronic diseases.